Knowledge, attitude and practice among non-ophthalmic health care providers regarding eye management of diabetics in private sector of Riyadh, Saudi Arabia - Talal Bassam Abu-Amara; Waleed Abdulaziz Al Rashed; Rajiv Khandekar; Hamad Mohammed Qabha; Faris Mohammad Alosaimi; Abdulrahman Abdullah Alshuwayrikh; Mansour Khalid Almadi; Alanoud Alfaris (BMC, 2019)
Abstract Background The levels of knowledge, attitude and practice among primary physicians concerning both diabetic retinopathy screening and treatment of sight threatening diabetic retinopathy have been studied by different groups, such as medical students, pharmacists, Primary Health Care staff and opticians. In some studies, the levels were very high, while in others it was noted to be less than desired. Aim This study's intent is to estimate and improve level of Knowledge (K), Attitude (A) and Practice (P) among non-ophthalmic health care providers regarding eye management of diabetes and barriers that people with diabetes face in Saudi Arabia. Methods This cross-sectional survey targeted medical doctors (except ophthalmologists) working at private sector institutions in Riyadh. They were interviewed using closed-ended questions for knowledge (8), attitude (5), practice (5), and reasons for their current KAP status comprised of 8 questions. The level of Knowledge was assessed as good if its score was (> 50%); positive attitude (> 50%) and excellent practice (> 75%) were estimated and associated to the risk factors. Results Out of the 355 participants that were interviewed, the percentages of good knowledge, positive attitude and excellent practice concerning diabetic retinopathy (DR)were 193 [54.3% (95% CI 49.2-59.5)], 111 [31.3% (95% CI 26.4-36.1)], and 145 [40.8% (95% CI 35.7-46.0) participants, respectively. Gender, place of work and type of doctor were not significantly associated with the level of KAP. Salient reasons for low KAP status included a busy schedule (54.6%), less resources (75.2%), inadequate periodic training in eye care (69%), and absence of retinal evaluation training (49.6%). Conclusions Improving KAP level is urgently needed. Addressing underlying causes of low KAP could enhance eye care of people with diabetes. Additionally, training for primary health care providers for early detection of DR and timely management of sight threatening diabetic retinopathy (STDR) is necessary.